0538 "Something is Wrong!" A Qualitative Study of Racial Disparities in Parental Experiences of OSA Detection among Their Children. (25th May 2022) - Chung, Alicia; Farquharson, Leone; Gopalkrishnan, Akila; Seixas, Azizi; Jean-Louis, Girardin; Honaker, Sarah
Abstract: Introduction: Blacks are 4-6 times more likely to have obstructive sleep apnea (OSA) than white children. Yet disparities in detection, diagnosis and treatment persist. Our study objective was to examine parents' perceptions and experiences with OSA detection among their children. Methods: Semi-structured phone interviews were conducted with 30 parents of children (ages 2-12 years) who were referred for overnight polysomnography due to OSA. Parents who identified as Black non-Hispanic (n=19) or White non-Hispanic (n=8) were included in the current analysis. Qualitative thematic analysis was conducted using a grounded theory approach, with themes organized in NVivo 12 software. Twenty-one themes falling into five categories were identified. To examine racial/ethnic disparity in parental experiences, themes were classified as convergent (presented by Black and White parents) or divergent (presented by one racial/ethnic group but not the other). Results: Participating parents were primarily mothers (92.59%). Children were 51.90% female; aged range from 3 to14 years old (M=7.93 years, SD=3.08). Delayed OSA detection was observed among Black children (M=9.00 years), compared to white children (M=5.78 years). Analysis of themes by race/ethnicity identified both shared experiences and perspectives, as well as those that were specific to or more salient for parents of one race. Convergent themes that overlapped among both groups included "Wanting to Know, Worries, and Child Daytime Symptoms." Divergent themes experienced by White caregivers included "Low threshold for raising concerns with provider, Institutional delays, and Trust in provider." "Misplaced blame, Whatever it Takes, Something is wrong, OSA Awareness, and Missing the day-night connection, " were divergent themes named by Black parents/caregivers. Conclusion: Black and white parents experience different paths to detection and diagnosis for their child's OSA, which may be affected by individual awareness, education, patient-provider interactions and experience with the healthcare system. Support (If Any): Research is supported by K23HL150290